(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
ischemic strokes (IS) at a young age are one of the pressing problems of modern reality, since they develop in people of working age. These vascular accidents are of great economic importance. Lacunar stroke (LI) due to small vessel occlusion is one of the main subtypes of IS with a variety of modifiable risk factors for its development.